Infeksi Ascaris lumbricoides dengan Jumlah Eosinofil pada Stunting di Desa Noelbaki Kabupaten Kupang Nusa Tenggara Timur - Mely Bria; Karol Octrisdey (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Worm disease is included in the neglected diseases group, which is a chronic infection that often does not show clear symptoms and the impact is only felt in the long term. Worms included in the Soil Transmitted Helminths (STH) group can spread through the soil and include Ascaris lumbricoides, Trichuris trichiura, hookworms (Necator americanus and Ancylostoma duodenale), and Strongyloides stercoralis. This worm infection can cause malnutrition, impaired child growth, decreased cognitive abilities, iron deficiency anemia, and reduced learning performance. One indicator of worm infection is an increase in eosinophil levels, which are part of the body's immune system. This study aims to analyze the relationship between Ascaris lumbricoides infection and the number of eosinophils in stunted children in Noelbaki Village, Kupang Regency, East Nusa Tenggara. This study used an analytical observational design with a case-control study approach, involving stunted children as subjects. The results showed the prevalence of Ascaris lumbricoides eggs of 51.3%, and an increase in abnormal eosinophils of 87.5% in cases of infection. Statistical tests revealed a significant relationship between A. lumbricoides infection and eosinophil count (p = 0.000). However, this study did not consider the possibility of allergy as a factor in increasing eosinophils.